2014
DOI: 10.4103/1319-2442.124499
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the microbiological quality of dialysate and treated water

Abstract: During hemodialysis and related therapies, removal of waste products from the blood is made possible across a semi-permeable membrane. The microbiological quality of treated water (TW) and dialysate influences a number of dialysis-related complications. This article is a review of the microbiological features of TW and dialysate fluid over a six-year period (February 2007 to December 2012) in the Dialysis Unit, 1st Medico-Surgical Hospital, Agadir, Morocco. Installation of a water treatment unit has been follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Therefore, the presence of all these bacterial varieties with resistant strains in treated water is a matter of concern in HD centers and should be taken seriously when assessing HD water quality by performing routine monthly disinfections with high-level disinfectants. Other solutions to improve the quality of HD water were recommended: disinfecting machines frequently by updating the disinfection protocol (Asserraji et al 2014;Verma 2015), biofilm analysis on tubing dialysis machines (Marion-Ferey et al 2003), improving nursing education on dialysis water (Chamney & James 2008), and conducting monthly quality assurance for risk analysis to the progress of water quality. The choice of piping materials is also essential.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of all these bacterial varieties with resistant strains in treated water is a matter of concern in HD centers and should be taken seriously when assessing HD water quality by performing routine monthly disinfections with high-level disinfectants. Other solutions to improve the quality of HD water were recommended: disinfecting machines frequently by updating the disinfection protocol (Asserraji et al 2014;Verma 2015), biofilm analysis on tubing dialysis machines (Marion-Ferey et al 2003), improving nursing education on dialysis water (Chamney & James 2008), and conducting monthly quality assurance for risk analysis to the progress of water quality. The choice of piping materials is also essential.…”
Section: Discussionmentioning
confidence: 99%
“…International studies carried out in Morocco, Nigeria, and Iraq (Al-Naseri, Mahdi, Hashim, 2013;Asserraji et al, 2014;Braimoh et al, 2014;Okunola, Olaitan, 2016) showed a high bacterial contamination of dialysis water in the dialysis units evaluated though do not reference endotoxin determination and total coliform research. Instead better water quality was observed by Totaro et al (2017) in a study with satisfactory results for 78% of the dialysis water samples evaluated monthly in nine Italian hospitals from 2015 to 2016.…”
Section: Introductionmentioning
confidence: 99%